Erythema Ab Igne due to Heating Pad Use: A Case Report and Review of Clinical Presentation, Prevention, and Complications - Marissa Milchak; Joanne Smucker; Catherine G. Chung; Elizabeth V. Seiverling (Case Reports in Medicine)
Erythema ab igne is an asymptomatic cutaneous condition caused by exposure to heat. Cases of erythema ab igne may prove to be diagnostically challenging due to lack of familiarity with the condition. While this dermatosis carries a favorable prognosis, nonmelanoma skin cancers have been reported to arise within lesions of erythema ab igne. Erythema ab igne is preventable, and, thus, clinicians should provide education regarding safe use of heating devices to patients using these products in both outpatient and inpatient settings.